Pressure on the labour market during the pandemic - Mikkel Bess; Simon Juul Hviid; Erik Grenestam; Filip Rozsypal (Danmarks Nationalbank, 2022)
The Danish labour market has tightened substantially during the recovery of the Danish economy. Pandemic-related labour demand can account for some of the employment growth. The majority of the movements on the labour market have occurred among marginal jobs, and cross-sectoral movements have been slightly higher than usual.
Keywords: 330; Other economic analyses; Economic activity and employment